Generation Z's Readiness for the Gig Economy: The Role of Digital Literacy, Self-Efficacy, and Career Orientation - Reska Rahmatullah; Ghia Subagja; Lina Dameria Siregar; Ahmad Khoirun Najib (Journal of Economics and Management Scienties, 2026)
Gig economy continues to expand rapidly, reshaping employment patterns among young generations, particularly Generation Z raised in digital environments. This study investigates the effects of digital literacy, self-efficacy, and career orientation on university students’ readiness for the gig economy. A quantitative approach was employed involving 227 Generation Z students from Universitas Sriwijaya. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The measurement model demonstrated strong validity and reliability, with factor loadings above 0.70, AVE values exceeding 0.50, and composite reliability above 0.90. The structural model showed substantial explanatory power (R² = 0.639; Q² = 0.403). Self-efficacy (β = 0.356) and career orientation (β = 0.358) emerged as the strongest predictors, while digital literacy also had a significant effect (β = 0.195). These findings highlight that gig economy readiness is shaped by the integration of digital competence, psychological capacity, and career clarity, underscoring the importance of strengthening digital literacy, self-efficacy development, and career planning services in higher education.